Evaluation of Sentinel Lymph Node Dose Distribution in 3D Conformal Radiotherapy Techniques in 67 pN0 Breast Cancer Patients - Gerlo Witucki; Nikolaus Degregorio; Andreas Rempen; Lukas Schwentner; Dirk Bottke; Wolfgang Janni; Florian Ebner (International Journal of Breast Cancer)
Introduction. The anatomic position of the sentinel lymph node is variable. The purpose of the following study was to assess the dose distribution delivered to the surgically marked sentinel lymph node site by 3D conformal radio therapy technique. Material and Method. We retrospectively analysed 70 radiotherapy (RT) treatment plans of consecutive primary breast cancer patients with a successful, disease-free, sentinel lymph node resection. Results. In our case series the SN clip volume received a mean dose of 40.7 Gy (min 28.8 Gy/max 47.6 Gy). Conclusion. By using surgical clip markers in combination with 3D CT images our data supports the pathway of tumouricidal doses in the SN bed. The target volume should be defined by surgical clip markers and 3D CT images to give accurate dose estimations.